The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.4028/www.scientific.net/msf.924.196
|View full text |Cite
|
Sign up to set email alerts
|

Optical Stressing of 4H-SiC Material and Devices

Abstract: Electrical testing with regard to bipolar degradation of high voltage SiC devices cannot be done on wafer level, but only expensively after module assembly. We show that 4H-SiC material can be optically stressed by applying high UV laser intensities, i.e. bipolar degradation as in electrical stress tests can be provoked on wafer level. Therefore, optical stressing can be used for control measurements and reliability testing. Different injection (=stress) levels have been used similar to the typical doping leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In collaboration with an Erlangen metrology company a tool for fast structural characterization of SiC wafers based on UVPL imaging was developed. With this tool SiC wafers up to 200 mm in diameter can be studied in‐line, non‐destructively and without preparative effort within minutes . By scanning the substrate directly after the epi‐process with the UVPL scanner it was possible to predict which devices would later drift due to bipolar degradation, and which devices would exhibit reliable behavior.…”
Section: Development Of Wide Bandgap Semiconductors (Sic Gan Aln)—cmentioning
confidence: 99%
“…In collaboration with an Erlangen metrology company a tool for fast structural characterization of SiC wafers based on UVPL imaging was developed. With this tool SiC wafers up to 200 mm in diameter can be studied in‐line, non‐destructively and without preparative effort within minutes . By scanning the substrate directly after the epi‐process with the UVPL scanner it was possible to predict which devices would later drift due to bipolar degradation, and which devices would exhibit reliable behavior.…”
Section: Development Of Wide Bandgap Semiconductors (Sic Gan Aln)—cmentioning
confidence: 99%
“…In the paper by Ishigaki et al that investigated the forward bias degradation of approximately 10,000 SiC MOSFET modules, a 10 % increase in V(on) voltage was reported for 2-3% of the modules [3]. Kallinger et al showed that BPDs inside epi-layer on 4H-SiC substrate were optically stressed by applying high UV laser irradiation, which can induce expand 1-SSF from the BPD at the wafer level similar to electrical burn-in testing [4]. Our proposed S-EVC method can detect not only the BPDs inside epi-layer but also the TED-converted BPDs that expand to bar shaped SSFs.…”
Section: Introductionmentioning
confidence: 99%